IMAGE-BASED ROADWAY ASSESSMENT WITH CONVOLUTIONAL NEURAL NETWORKS - Abhishek Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
This shortfall, alternatively, arises, in a large part, through inefficiencies that may be inherent in traditional fixed spectrum management regulations. This is due to the fact that studies have confirmed that the lack of spectrum is fake. Improvements in cell communication over the past three decades have been accompanied by a huge increase in demand for bi-directional cellular communication services everywhere in the world. As of 2011, there are over four billion cellular subscribers internationally, million radio base station locations. Mobile and broadband visitor volumes continue to grow, requiring additional investments in network capacity, new spectrum for brand spanking, and requirements for advanced air interfaces that allow for accelerated energy and can provide spectral efficiency. In percentage terms, the amount of electricity or spectrum used and associated fees regularly climbs grows which is carried over the network.